Exploration of Work Accident Prevention Behavior Among Technical Service Personnel In the Implementation of The 'One Pict Saves You' Movement at PT PLN (Persero) Customer Service Unit Bireuen - Ricky Gunawan; Bobby W. Saputra (Publikasi Indonesia, 2024)
This study aims to explore the work accident prevention behaviors of technical service officers in response to the implementation of the